2020
DOI: 10.1007/s10549-020-05727-x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between young and old patients with triple-negative breast cancer: biology, survival and metastatic patterns

Abstract: Purpose To determine the biology, recurrence rate, metastatic patterns and survival times in primary triple-negative breast cancer (TNBC) with focus on the comparison between younger and elderly patients. Methods Patients with primary TNBC stage I-IV diagnosed from 2007 to 2015 were identified and information on tumor biology, stage, treatment, recurrences and death recorded. Results A total of 524 patients, median age 60 years (range 24-94) with a median follow-up of 55 months (range 0-129) were identified. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 29 publications
(40 reference statements)
2
51
3
1
Order By: Relevance
“…Moreover, we also found that breast cancers of post-menopausal patients tended to have high densities of nerves, suggestive of poorer prognosis of these patients. Indeed, older breast cancer patients commonly have worse survival than those diagnosed at younger ages [50,51]. Nevertheless, we did not identify differences in breast cancer innervation among different age groups.…”
Section: Discussioncontrasting
confidence: 56%
“…Moreover, we also found that breast cancers of post-menopausal patients tended to have high densities of nerves, suggestive of poorer prognosis of these patients. Indeed, older breast cancer patients commonly have worse survival than those diagnosed at younger ages [50,51]. Nevertheless, we did not identify differences in breast cancer innervation among different age groups.…”
Section: Discussioncontrasting
confidence: 56%
“…Indeed, older breast cancer patients commonly have worse survival than those diagnosed at younger ages. 46,47 Nevertheless, we did not identify differences in breast cancer innervation among different age groups. What causes these paradoxes is unknown, but our results suggest that the innervation status be considered in stratifying patients in future studies.…”
Section: High Nerve Trunk Density In Breast Cancer May Predict Poorer...contrasting
confidence: 55%
“…This may reflect the poor prognosis for young adults with cancers, such as breast cancer [23] and colorectal cancer [24]. Breast cancers in young adults have a higher incidence of the more aggressive triple-negative form and are less hormonesensitive than those in older adults [25]. As to colorectal cancers, they have a more mucinous histology and greater frequency of signet ring cells in young adults than in older adults, resulting in a markedly poor prognosis [26].…”
Section: Discussionmentioning
confidence: 99%